A Comparative Clinical Study to Evaluate the Efficacy of Sitopaladi Churna and Vishwadi Churna in the Management of Vataja Kasa - Hajare, Gajanan Wamanrao (International Research Journal of Ayurveda & Yoga, 2023)
Background: Vataja Kasa seems to be very simple disease, if not controlled and treated properly it may lead to disease with poor prognostic condition. Hence, we are in demand of a quick-acting medicine with higher effectiveness, search of such a medicine end up with Vishwadi Churna is taken as a standard drug to compare and assess the trial drug. Materials and Methods: Twenty patients of Group A were treated with Sitopaladi Churna for 30 days. Twenty patients of Group A were treated with Vishwadi Churna for 30 days. Twenty patients in each group and both groups subjected to Vataja Kasa management. In the first group doses of Sitopaladi Churna in dosage of 2 g thrice a day with Sukoshna jala for 30 days and in the second group Vishwadi Churna in dosage of 2 gm thrice a day with Sukoshna jala. In this study, various observations of geographical elements such as age, gender, and Religion are presented in the form of diagrams, charts, etc. Results: The result of both the groups was analyzed statistically compared and the results were interpreted in the term of increase or decrease in the parameter. Conclusion: From the statistical analysis, Sitopaladi Churna is more effective than Vishwadi Churna in Vataja kasa.